(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: The risk of having ovarian tumor in female at sometime in her life is 6-7%. Relative frequency of ovarian tumor is different for Western and Asian countries. Identification of various histological patterns is important for correct diagnosis, which further affects treatment and prognosis. Objective: To evaluate the frequency of histological patterns of ovarian tumors in women presenting in a tertiary care hospital. Methodology: This descriptive cross-sectional study included 100 cases of ovarian tumors reported in department of pathology, Fatima Jinnah Medical College/Sir Ganga Ram Hospital, Lahore. SPSS version 20 was used for analysis of data. Results: Out of 100 ovarian tumors included, 52% were benign and 48% were malignant. Mean age was 35 years ranging from 10 to 70 years. Surface epithelial tumors were most common (62%) followed by germ cell tumors 32%. Most frequently occurring benign tumor was serous cystadenoma (20%) while malignant tumor was serous cystadenocarcinoma (25%). Conclusion: Benign tumors outnumbered malignant tumors but this difference was not very large. Surface epithelial tumors were most common type. Serous cystadenoma was most common benign tumor and serous cystadenocarcinoma was most common malignancy.